2002
DOI: 10.1016/s0969-6997(01)00050-3
|View full text |Cite
|
Sign up to set email alerts
|

Price elasticities of demand for passenger air travel: a meta-analysis

Abstract: The demand for air transport is largely determined by the spending capacity of customers. This paper aims to offer more insight into the determinants of price elasticities in the aviation sector. It seeks to identify both common and contrasting factors that influence the price elasticities, on the basis of a comparative analysis among a large number of empirical studies in this field. By means of meta-analytical methods the relative importance of several driving forces (e.g., distance, type of ticket, nature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
166
1
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(187 citation statements)
references
References 3 publications
13
166
1
7
Order By: Relevance
“…The parameters and equilibrium outputs are: Airlines' operating cost parameters are from Swan and Adler (2006), using a reference distance of 1.500 km and an adjustment in the per-passenger cost as suggested by the authors. Values of time are from Morrison and Winston (1989), while congestion, delay and demand parameters are set such that equilibrium elasticity with respect to generalized price in both settings is close to -1.146, the mean value of 204 observations reported by Brons et al (2002). Values are set to the same monetary units (U.S. dollars) throughout the calibration process.…”
Section: Numerical Analysismentioning
confidence: 99%
“…The parameters and equilibrium outputs are: Airlines' operating cost parameters are from Swan and Adler (2006), using a reference distance of 1.500 km and an adjustment in the per-passenger cost as suggested by the authors. Values of time are from Morrison and Winston (1989), while congestion, delay and demand parameters are set such that equilibrium elasticity with respect to generalized price in both settings is close to -1.146, the mean value of 204 observations reported by Brons et al (2002). Values are set to the same monetary units (U.S. dollars) throughout the calibration process.…”
Section: Numerical Analysismentioning
confidence: 99%
“…A recent meta-analysis of air travel price-elasticity studies showed that long distance travel is less price-elastic (i.e. sensitive) than short distance travel, possibly because the choices and possibilities for substitution are fewer (Brons et al, 2002). Brons et al also found that air travellers have become less pricesensitive over the last two decades, maybe reflecting the increasing use of air travel by the wider society.…”
Section: Introductionmentioning
confidence: 99%
“…Brons et al also found that air travellers have become less pricesensitive over the last two decades, maybe reflecting the increasing use of air travel by the wider society. It also seemed that travellers are less likely to decrease demand immediately, but will react more sensitively in the long run when they have had time to adjust to the new prices (Brons et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…An assessment of determinants and motivators needs to be accompanied by consideration of the specific role which air transport plays within leisure travel and the multiple levels of product substitution which exist (Brons et al, 2002). At the most general level, leisure travel can compete with other home-based leisure activities and the purchasing of travel products can be seen as just one of many spending options which consumers have with their disposable income.…”
Section: Introductionmentioning
confidence: 99%